Re-interpreting Brecht: his influence on contemporary drama and film - Kleber, Pia; Visser, Colin (Cambridge, New York: Cambridge University Press, 1990)
This volume offers a fresh appraisal of the importance of Bertolt Brecht's theory and practice through the documentation of his influence on other dramatists and directors, the examination of how his plays have been interpreted on stage and how his theories have been modified by his followers, and through a selection of the most challenging recent critical approaches to his work.